2008
DOI: 10.1590/s0101-81082008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Depressão em mulheres climatéricas: análise de mulheres atendidas ambulatorialmente em um hospital universitário no Maranhão

Abstract: Introdução: O climatério, período de transição entre a fase reprodutiva e não-reprodutiva, ocasiona mudanças biopsicossociais nas mulheres que o vivenciam. A associação entre a maior prevalência de depressão nesse período é, no entanto, ainda controversa. O objetivo deste estudo foi avaliar a prevalência de depressão em mulheres climatéricas atendidas em um hospital universitário numa cidade da Região Nordeste do Brasil e identificar fatores associados. Método: Foi realizado um estudo prospectivo e analítico d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
4
1
9
Order By: Relevance
“…[7] Concerning marital status, found a favorable situation because women in stable marital relationships are less likely to develop depressive symptoms. [5,14] In this study, the prevalence of depressive symptoms was high (68.1%), surpassing the findings of other studies. [4,13,15,16] This may reflect the economic reality of the studied population.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…[7] Concerning marital status, found a favorable situation because women in stable marital relationships are less likely to develop depressive symptoms. [5,14] In this study, the prevalence of depressive symptoms was high (68.1%), surpassing the findings of other studies. [4,13,15,16] This may reflect the economic reality of the studied population.…”
Section: Discussioncontrasting
confidence: 89%
“…The average age of respondents corresponds to the menopausal transition, marked by variation of the menstrual flow (amenorrhea, polymenorrhea), and was lower than in other population-based studies examining the relationship between menopause and depressive symptoms, [5,[13][14] thus allowing inferences about the early age at which such changes arise in the population studied. The education level of the participants was considered to be low.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…According to the WHO [15] depression is the 4 th world cause of social incapacitation and the main public health problem worldwide, with an estimated prevalence of depressive disorders among the elderly being between 10 and 20%, depending on the cultural situations. In an prospective, analytic study of 70 climacteric women, Silva et al [16] verified a high prevalence of depression in the evaluated patients, observing a percentage of 34.3% of depression, and 70.8% were classified as mild intensity according to Hamilton scale. According to the authors, an association was found between the presence of depression and patients with vasomotor symptoms (p = 0.03), insomnia (p <0.001), menopause (p = 0.05), with a history of post-partum depression (p = 0.04) and premenstrual dysphoric disorder (p = 0.05) and negative menopausal vision (p = 0.001).…”
Section: Discussionmentioning
confidence: 92%
“…Inicialmente foi encaminhada cópia do projeto de pesquisa para avaliação SILVA et al, 2008;POLISSENI et al, 2009 Mesmo sendo uma fase comum a todas, na presente pesquisa observouse que havia certo desconhecimento por parte de algumas mulheres participantes sobre o termo "climatério" e, em relação à "menopausa", a maioria das mulheres compreende que esta envolve a parada da menstruação, como descrito nas falas:…”
Section: Aspectos éTicos Da Pesquisaunclassified